2016
DOI: 10.1111/cdev.12572
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing in Rhesus Monkeys: Developmental Continuity, Prenatal Treatment, and Genetic Influences

Abstract: Neonatal sensory processing (tactile and vestibular function) was tested in 78 rhesus macaques from two experiments. At ages 4–5 years, striatal dopamine D2 receptor binding was examined using positron emission tomography. At ages 5–7 years, adult sensory processing was assessed. Findings were: (a) prenatal stress exposure yielded less optimal neonatal sensory processing; (b) animals carrying the short rh5-HTTLPR allele had less optimal neonatal sensory scores than monkeys homozygous for the long allele; (c) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Probably due to the small sample used in this research, this study has not yielded statistically significant differences between children who have suffered from a stressful/traumatic pregnancy and tactile and auditory sensory processing, expected results following the findings obtained by Keuler et al [24], who drew a relationship between prenatal complications and problems of auditory and tactile hyperreactivity. These results [30] are a finding compatible with the research of Schneider et al [11] in rhesus monkeys, thus suggesting that prenatal maternal stress increases babies' tactile sensitivity, and the study by Heuvel, Donkers, Winkler, Otte & Van Der Bergh [25], which indicates that greater maternal anxiety could be interpreted as a reflection of weaker habituation to auditory stimuli in these babies, thus indicating less adaptive brain functioning.…”
Section: Resultssupporting
confidence: 91%
“…Probably due to the small sample used in this research, this study has not yielded statistically significant differences between children who have suffered from a stressful/traumatic pregnancy and tactile and auditory sensory processing, expected results following the findings obtained by Keuler et al [24], who drew a relationship between prenatal complications and problems of auditory and tactile hyperreactivity. These results [30] are a finding compatible with the research of Schneider et al [11] in rhesus monkeys, thus suggesting that prenatal maternal stress increases babies' tactile sensitivity, and the study by Heuvel, Donkers, Winkler, Otte & Van Der Bergh [25], which indicates that greater maternal anxiety could be interpreted as a reflection of weaker habituation to auditory stimuli in these babies, thus indicating less adaptive brain functioning.…”
Section: Resultssupporting
confidence: 91%
“…These females were then randomly assigned to consume alcohol during specific gestation periods, alone or in combination with mild prenatal stress exposure, compared with randomly assigned controls. We did not include the prenatal treatment findings in this paper because they have been reported elsewhere (Schneider et al, 2008a, 2009, 2017; Converse et al, 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly interested in PFC and striatum and their sub-regions because of their critical role in organizing complex cognitive function and translating stimulus properties into adaptive behavior, as well as midbrain, the location of DA cell bodies. In this paper we examined the relationships of ligand binding to our findings from the SPS-M (Schneider et al, 2008b), concentrating on brain regions that had shown effects of DA in our previous work (Schneider et al, 2008a, 2017; Converse et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In primate models, certain genes (e.g. the short serotonin transporter gene polymorphic region variation [rh5‐HTTLPR]), an allele with a functional analog in humans) increase the likelihood of developing sensory [163], stress and irritability [164] disorders secondary to alcohol. As noted previously, genes that code for alcohol dehydrogenase polymorphisms may affect drinking behavior or alcohol metabolism, impacting on the amount of maternal alcohol reaching the fetus [165].…”
Section: Fetal Alcohol Spectrum Disorder (Fasd)mentioning
confidence: 99%